First cobalt(II) spin crossover compound with N4S2‐donorset - Fuermeyer, Fabian; Muenzberg, Danny; Carrella, Luca M.; Rentschler, Eva (Molecules, 2020)
Herein we report the synthesis and characterization of a novel bis‐tridentate 1,3,4-thiadiazole ligand (L = 2,5‐bis[(2‐pyridylmethyl)thio]methyl‐1,3,4‐thiadiazole). Two new mononuclear complexes of the type [MII(L)2](ClO4)2 (with M = FeII (C1) and CoII (C2)) have been synthesized, containing the new ligand (L). In both complexes the metal centers are coordinated by an N4S2‐donorset and each of the two ligands is donating to the metal ion with just one of the tridentate pockets. The iron(II) complex (C1) is in the low spin [LS] state below room temperature and shows an increase in the magnetic moment only above 300 K. In contrast, the cobalt(II) complex (C2) shows a gradual spin crossover (SCO) with T1/2 = 175 K. To our knowledge, this is the first cobalt(II) SCO complex with an N4S2‐coordination.
CRIS-Team Scopus Importer:2023-03-27
Keywords: 1; 3; 4-thiadiazole; Cobalt(II); Iron(II); magnetism; N4S2-donorset; Spin crossover